Duplo grau de jurisdição: compreensão constitucional do princípio e análise de tema sob a perspectiva das reformas introduzidas no código de processo civil pela Lei 10352/01 - Passos, Aline Araújo (2005)
This paper deals with the principle of the appellate jurisdiction, and attempts to construe it from the perspective of the 1988 Federal Constitution, offering as well a critique of recent changes introduced in the Procedural Civil Law Code by statute number 10.352 of December 26th, 2001, specially the ones made in articles 475 and 515. The reason for the choice of the current subject was influenced by the study of Procedural Constitutional Law, which led to an even deeper analysis whose conclusions encompass both Constitutional and Procedural Law. It was precisely the possibility of this remarkably updated interdisciplinary study that made this paper possible. Discussing the full implication and outreach of the appellate jurisdiction principle means to question the very behavior of the State, under the rule of law, in relation to its citizens since such a right prevents them from State arbitrary power and enables the revision and adjudication by a higher court of any matter that has been tried in a court of original jurisdiction. Needless to say that the State is well-known for being the most encompassing defendant in the country. The restrictions brought about on the principle of the appellate jurisdiction by the new statute rekindle the old-time debate, which has inflamed so many scholars around the world, over how to reconcile judicial predictability and procedural celerity, which aims at an effective judicial protection. In order to properly answer whether the changes brought about by statute 10.352/01 are constitutional or not, it was necessary to follow a long path of document and bibliography research which included the study of principles in general, above all the constitutional principles with special focus on the definition and outreach of the appellate jurisdiction principle. It also involved analyzing and establishing relationship between that principle and the existing Appeals, as well as the constitutional exam of the mandatory review law, its legal exceptions that represent a limit or a suppression of the aforementioned guarantee. Based on this study we came to the conclusion that the command of the article 515, # 3rd of the statute 10.352/01, as well as the mandatory review law are unconstitutional. Although following different way of reasoning, we based both conclusions on the unshakable grounds of the Major Law.